Development and Validation of an Augmented Reality-Based Career Card Game for Student Career Guidance - Syahira, Syahira; Nur Fadhilah Umar; Akhmad Harum (Indonesian Journal of Learning Education and Counseling, 2025)
This study aims to develop and evaluate augmented reality-based career card games as a career information tool for high school students. The research method uses a modified Borg & Gall research and development model, with stages including needs analysis, product design, expert validation, and practicality testing. Data were obtained through questionnaires and interviews, then analyzed descriptively and quantitatively. The results showed that students need career guidance media that is more interesting, interactive, and technology-based. The AR Career Explorer product was declared highly valid and practical by experts, guidance counselors, and students. The novelty of this study lies in the integration of Holland's theory with AR technology in the form of a card game, which has not been found in previous studies. This media is suitable for use as an innovative alternative to improve career information services in high schools.